2021
DOI: 10.1111/jocn.15857
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personal protective equipment and social distancing on communication and relation between nurses, caregivers and children: a descriptive qualitative study in a maternal and child health hospital

Abstract: Aims and objectivesThe main objective was to explore the impact of personal protective equipment and social distancing on nurses, caregivers and children's communication and relationship in a maternal and child health hospital.BackgroundThe spread of COVID‐19 pandemic made it necessary to apply infection prevention and control measures, including interpersonal distancing and the use of personal protective equipment. These measures may impact communication and relationship between nurses, patients and caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…With the exception of two, all were survey-based studies ( 24 , 26 , 32 37 ). The two exceptions used semi-structured interviews, with one supplementing this with information from media reports and government policies ( 31 , 38 ). Nine of the ten studies reported that PPE and/or distancing caused barriers to effective verbal and non-verbal communication with patients, especially for HCPs who are D/deaf ( 26 ), and that it negatively impacted psychosocial factors such as trust and rapport, and resulted in patients (including pediatric patients) feeling fearful/anxious during appointments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of two, all were survey-based studies ( 24 , 26 , 32 37 ). The two exceptions used semi-structured interviews, with one supplementing this with information from media reports and government policies ( 31 , 38 ). Nine of the ten studies reported that PPE and/or distancing caused barriers to effective verbal and non-verbal communication with patients, especially for HCPs who are D/deaf ( 26 ), and that it negatively impacted psychosocial factors such as trust and rapport, and resulted in patients (including pediatric patients) feeling fearful/anxious during appointments.…”
Section: Resultsmentioning
confidence: 99%
“…Masks have always been a part of medical practice, however, their now ubiquitous use has had broad impacts on communication within the medical context. In addition to detrimental effects on verbal interactions, masks have been reported to affect HCP-HCP and HCP-patient interpersonal relationships, decrease trust and perceived empathy, create fear and anxiety in patient, and reduce HCP's situational awareness-all of which can subsequently affect quality of care ( 24 , 28 , 30 , 31 , 33 , 34 , 36 , 38 ). Indeed, Trecca and colleagues ( 62 ) reported that more patients with hearing loss attributed problems with surgical masks to the inability to lip read than to the speech being muffled, while the study of Kratzke et al ( 36 ) found patients perceived HCPs to be more empathetic and trustworthy than when they are wearing transparent masks rather than opaque masks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies are limited to needs of a specific group, often those with particular morbidities or life-situations (see Giannakopoulos et al, 2021 ; Mirlashari et al, 2021 ; Sharma et al, 2020 ; Tse et al, 2021 ). In addition, only a minority of studies are based on data generated directly by children or adolescents, with most instead relying on proxy reports from teachers, parents and other sources ( Berasategi Sancho et al, 2021 ; Evans et al, 2020 ; Ferrari et al, 2021 ; Ferraro et al, 2021 ; Fitzpatrick et al, 2020 ). In general, the extant research is framed by professionalized knowledge and frameworks, with few open explorations of salient issues from the perspectives of children or adolescents themselves.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…Nurses knows that the presence of the family with the child throughout the hospitalization facilitates the child's involvement and participation in the care received, reducing levels of stress and anxiety for the child, with the parents' absence. The authors also describe this issue and their implications in health professional education, which an opportunity to create new communication approaches in hospital setting between nurses, children and parents (Al-Motlaq et al, 2021;Ferrari et al, 2021). The strategies used by nurses wearing masks and other personal protective equipment to facilitate verbal and nonverbal communication include involve family (parents/caregivers) are explain to parents the role of play in these circumstances; use a technological dispositive of communication; promoting parental support among other strategies (Al-Motlaq et al, 2021;Carter et al, 2021;Ferrari et al, 2021).…”
mentioning
confidence: 99%